Heritage Management at the Local Level: Heritage Communities and Role of Local Authorities - Jelka Pirkovič (University of Belgrade, 2020)
Heritage management at the local level benefits heritage properties and serves the public interest. By using comparative and interpretative analyses, we argue for the use of the “heritage community” term in current heritage management, and analyse what this expression brings for the role of local authorities. We upgrade this definition with attributes that characterize heritage communities. The paper presents the evolution of the concept of participatory heritage management in the context of the Operational Guidelines for the Implementation of the World Heritage Convention. It tests the relevance of the participatory approach in the heritage field against the theory of social systems. Conclusions comprise principles defining the role of local authorities in facilitating direct participation of heritage communities in heritage management.